The Study of the Rate of TEC Index over Thailand - Buakao, Nitipat; Phothila, Prarinya; Kenpankho, Prasert (My University, 2025)
This study examines the variations in Rate of TEC Index (ROTI) across three provinces in Thailand-Bangkok, Chiang Mai, and Chumphon-using Total Electron Content (TEC) data derived from BG2s GPS receivers during the period from January to March 2025. ROTI values were classified into three levels: high (>0.8), moderate (0.4-0.8), and low (<0.4) TEC variability. The analysis revealed that Chumphon exhibited the highest TEC variability, followed by Bangkok and Chiang Mai. In January, Bangkok recorded elevated ROTI values between 14:25 and 15:25 local time, with lower values observed from midnight to noon and after sunset. In February, ROTI values exceeding 0.8 were detected between 13:00 and 20:00, with Chumphon showing the most intense fluctuations. In March, high ROTI values occurred from 13:00 to 22:00, with Bangkok experiencing the most prolonged periods of TEC disturbance. These results underscore the spatial and temporal dynamics of ionospheric irregularities in low-latitude regions and support the effectiveness of ROTI as a diagnostic tool for monitoring space weather impacts on GNSS signals.
Keywords: GNSS; Ionospheric Irregularities; Low-Latitude Region; Rate of TEC Index (ROTI); Space Weather; Thailand; Total Electron Content (TEC)